Aggressive Blood Pressure Lowing Therapy in Patients with Acute Intracerebral Hemorrhage is Safe: A Systematic Review and Meta-analysis - Pan, Chao (Chin Med J (Engl), 2015)
BACKGROUND: The influence of blood pressure (BP) lowering on intracerebral hemorrhage (ICH) patients is unclear. To assess the safety and efficacy of aggressive antihypertensive therapies in acute ICH patients, we carried out a systematic review and meta-analysis. METHODS: PubMed, EMBASE, Cochrane Library, China National Knowledge Infrastructure, and VIP database up to July 2014 were searched. High-quality randomized controlled trials were included. Low-quality trials were excluded. Serious adverse events were defined as the primary outcome. The secondary outcomes were hematoma enlargement (HE) at 24 h after onset, mortality, and favorable clinical outcome at 90 days. RESULTS: Four high-quality trials involving a total of 1427 patients met the inclusion criteria and were analyzed. Odds ratios (ORs) of primary outcome was 0.96 (95% confidence interval [CI ]: 0.82–1.13, P = 0.61). ORs of HE at 24 h after onset, mortality and favorable clinical outcome at 90 days were 0.91 (95% CI: 0.72–1.17, P = 0.47), 0.97 (95% CI: 0.79–1.20, P = 0.81), 1.13 (95% CI: 0.98–1.30, P = 0.09) respectively. CONCLUSIONS: Aggressive BP management policies are safe and might have a potency of reducing HE and improving clinical outcome.